Chemistry of Hetera-buckybowl Trichalcogenasumanenes - Li, Dongxu; Shao, Xiangfeng (Synlett, 2020)
Buckybowls attract significant attention in chemistry and materials science owing to their unique features related to both geometric and electronic aspects. Doping the π-skeleton of buckybowls with the main group elements results in hetera-buckybowls, and accordingly has a large influence on the chemical and physical properties. This account summarizes our research progress on hetera-buckybowl trichalcogenasumanenes (TCSs), including their synthesis, regioselective oxidations, transformation into various hetero polycycles (chiral π-systems, molecular spoons, etc.), and their application as optoelectronic materials.1 Introduction2 Synthesis of TCSs3 Structural and Electronic Features of TCSs4 Regioselective Oxidation of TCSs4.1 Cleavage of the Edged Benzene Rings4.2 Oxidation of the Thiophene Rings4.3 Transformation of Butoxy Groups into an ortho-Quinone4.4 Intermolecular Charge Transfer4.5 Influence of Chalcogen Atoms on Oxidation Reactions5 Synthesis of Hetero Polycycles from TCSs6 Optoelectronic Properties of TCSs and Their Derivatives7 Conclusion
Keywords: conjugated polycycles; buckybowls; hetera-sumanenes; trichalcogenasumanenes; chiral π-systems; molecular spoons; regioselective oxidation; optoelectronic properties